Typologia krajów według wskaźnika ESI (Environmental Sustainability Index) - Borys, Tadeusz; Markowska, Małgorzata (The typology of countries according to ESI (Environmental Sustainability Index), 2006)
The article presents concise characteristics of ESI formal concept as well as the typology of countries according to this indicator values, facilitated by the cluster analysis and study results referring to interrelations between ESI and GDP per capita levels. The ESI indicator in its 2005 version - understood as a sub-synthetic measure of sustainable development - is constructed by means of a two-level aggregation of 76 composite indicators. The construction of this indicator also enables aggregation within the range of the following five themes (components): “environmental systems”, reduction of environmental stresses”, “reduction of population susceptibility”, “social and institutional capacities” and “global management”.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 65-73